On the reinterpretation of architectural ugliness in recent German and Polish prose: Two case studies - Blidy, Monika (Porównania, 2024)
The discussion surrounding the architectural legacy of the twentieth century has long been characterized by a predominantly negative narrative, wherein prefabricated housing estates were viewed as an aesthetically and functionally questionable remnants of the bygone era, often associated with poverty and social pathology. As a kind of counter-draft to these discourses, a tendency has emerged in recent literature—especially in the last ten years—which focuses thematically on post-industrial places and not only demands a revision of the negative image of prefabricated housing, but also constructs its own visions of the high-rise building as a specific universe. Against this background, this paper aims to trace the aforementioned tendency in recent prose on the subject of prefabricated housing and to work out its characteristics on the basis of Polish and German case studies.